Phase IIIb safety results from an expanded-access protocol of talimogene laherparepvec for patients with unresected, stage IIIB–IVM1c melanoma. Issue 1 (February 2018) - Chesney, Jason; Awasthi, Sanjay; Curti, Brendan; Hutchins, Laura; Linette, Gerald; Triozzi, Pierre; Tan, Marcus C.B.; Brown, Russell E.; Nemunaitis, John; Whitman, Eric; Windham, Christopher; Lutzky, Jose; et al.
Abstract : Talimogene laherparepvec is a genetically modified herpes simplex virus-1-based oncolytic immunotherapy for the local treatment of unresectable cutaneous, subcutaneous, and nodal tumors in patients with melanoma recurrence following surgery. We aim to describe the safety of talimogene laherparepvec. Intralesional talimogene laherparepvec was administered at less than or equal to 4 ml×10 6 PFU/ml at protocol day 1, then less than or equal to 4 ml×10 8 PFU/ml 21 days later, and then every 14 days. Treatment continued until complete response, absence of injectable tumors, progressive disease, intolerance, or US Food and Drug Administration approval. Adverse events were graded during and 30 days after the end of treatment. Lesions suspected to have herpetic origin were tested for talimogene laherparepvec DNA by quantitative PCR (qPCR). Between September 2014 and October 2015, 41 patients were enrolled with stage IIIB (22%), IIIC (37%), IVM1a (34%), IVM1b (5%), and IVM1c (2%) melanoma. The median age was 72 (range: 32–96) years and 54% of the patients were men. Patients had an ECOG performance status of 0 (68%) or 1 (32%). The median treatment duration was 13.1 (3.0–41.1) weeks. Treatment-related adverse events of greater than or equal to grade 3 were reported in three (7.3%) patients and included vomiting, upper abdominal pain, chills, hyperhidrosis, nausea, pyrexia, and wound infection. Suspected herpetic lesions were swabbed in five (12%) patients. One of the five tested positive for talimogene laherparepvec DNA by qPCR, but this lesion had been injected previously with talimogene laherparepvec. During the study, five patients completed treatment because of complete response per investigators. In the clinical practice setting, talimogene laherparepvec has a safety profile comparable to that observed in previous clinical trials. Talimogene laherparepvec (IMLYGIC) is now approved in the US, European Union, and Australia.